Fire frequency effects on soil and pollinators: what shapes sexual plant reproduction? - Carbone, Lucas Manuel (2017)
Fil: Carbone, Lucas Manuel. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias; Argentina.